PEMBIAYAAN MURABAHAH DALAM PERBANKAN SYARIAH - Nasrulloh . (Journal of Management and Business, 2004)
Today, Islamic Bank, or better known as Muamalat Bank has been an interesting phenomenon. The Islamic Bank has It's own system, including the financing system. This financing system is known as "Murabahah". This paper describe about murabahah, start from its definition, legal aspect, murabahah mechanism, and law protection mechanism.The Author use example to improve the explanation. At the End the author analyze and summarize this financing system.